Ritual innovation in the Hebrew bible and early judaism - MacDonald, Nathan 1975- (Berlin/Boston De Gruyter, Inc., 2016)
The series Beihefte zur Zeitschrift für die alttestamentliche Wissenschaft (BZAW) covers all areas of research into the Old Testament, focusing on the Hebrew Bible, its early and later forms in Ancient Judaism, as well as its branching into many neighboring cultures of the Ancient Near East and the Greco-Roman world.
Intro -- Preface -- Table of Contents -- Strange Fire before the Lord: Thinking about Ritual Innovation in the Hebrew Bible and Early Judaism -- Two Types of Ritual Innovation for Profit -- From Ark of the Covenant to Torah Scroll: Ritualizing Israel's Iconic Texts -- The Empty Throne and the Empty Sanctuary: From Aniconism to the Invisibility of God in Second Temple Theology -- Ritual Innovation and Shavuʿ ot -- How the Priestly Sabbaths Work: Innovation in Pentateuchal Priestly Ritual -- Innovation in the Suspected Adulteress Ritual (Num 5:11-31) -- Practicing Rituals in a Textual World: Ritual and Innovation in the Book of Numbers -- Walking over the Dead: Burial Practices and the Possibility of Ritual Innovation at Qumran -- Contributors -- Subject Index -- Index of names.
Description based on publisher supplied metadata and other sources
Keywords: Judaism ; Customs and practices ; History; Electronic books; Konferenzschrift -- 2013 -- Saint Andrews